A propósito de la digitalización del dinero: las criptomonedas y su incidencia tributaria en el Perú. El caso del bitcoin - Román Yrigoín, Diana Elizabeth (2019)
In this investigation the legal and economic nature of cryptocurrencies is reviewed, with particular emphasis on bitcoin, in order to determine the tax impact of the corporate and personal income tax and the value added tax in the operations of buying and selling bitcoins, the ones in which they are used as a mean of payment and in the bitcoin mining service in Peru. In this context, we detail the legal devices that tax the operations with cryptocurrencies mentioned above with the Income Tax and the Value Added Tax, as well as the need for a special tax regulation in Peru for cryptocurrency operations.